Visualisasi Bidadari Surga Dalam Perspektif Al-Qur’an (Analisis Konstruksi Sosial Gender Dalam Tafsir Ath-Thabari) - Cyndiana Rustin Pratiwi; Siti Masykuroh; Fitri Windari; Suhandi (Jurnal test, 2025)
The visualization of the houris in the Qur’an is described as hur ‘in, women with beautiful eyes and clear skin like hidden pearls. They are portrayed as shy, loyal, and eternally youthful. This imagery reflects the social construction of gender that influences classical interpretations, particularly in Tafsir Ath-Thabari. This study analyzes Ath-Thabari’s interpretation of the concept of houris in paradise and re-examines it through the lens of Judith Butler’s theory of gender as a social construct. Butler asserts that gender is not a fixed biological category but a social construct shaped by culture, language, and discourse. The interpretation of houris is not merely textual but also shaped by the patriarchal gender norms prevalent at the time the interpretation was formulated. This research employs a literature review method with a descriptive and linguistic analysis approach to the Qur’anic verses and Ath-Thabari’s exegesis. The findings reveal that Ath-Thabari interprets the houris literally, emphasizing their physical and sensual attributes as a form of pleasure for faithful men. The depiction of houris with large, beautiful eyes, ideal body shapes, and pure white skin reflects the classical Arab standards of beauty. From Butler’s perspective, such interpretations are cultural constructions that reproduce gender hierarchies, rather than representing absolute realities.